29th Annual Conference of the German Crystallographic Society, March 15-18, 2021, Hamburg, Germany - Elektronen-Synchrotron-DESY, Deutsches (Zeitschrift für Kristallographie / Supplemente, 2021)
Zeitschrift für Kristallographie. Supplement Volume 41 presents the complete Abstracts of all contributions to the 29th Annual Conference of the German Crystallographic Society in Hamburg (Germany) 2021:- Plenary Talks- Microsymposia- Poster Session Supplement Series of Zeitschrift für Kristallographie publishes Abstracts of international conferences on the interdisciplinary field of crystallography.